Answer:
x = 2 ; y = 1
Explanation:
GIVEN :-
(eqn.1)
(eqn.2)
SOLUTION :-
The easiest way to solve such questions where two linear equations (with two variables) ax + by = c and bx + ay = d are given is :-
1) Add both the equations :-
![4x + 3y + 3x + 4y = 11 + 10](https://img.qammunity.org/2023/formulas/mathematics/college/cy2ivx09vztep9o9olcqvaq51qndsay119.png)
Simplify it further.
![7(x + y) = 21](https://img.qammunity.org/2023/formulas/mathematics/college/tdz85eqy9vz9xnbbyvh2pzguarahzgrlqa.png)
..... eqn.3
2) Substract both the equations :-
![4x + 3y - 3x - 4y = 11 - 10](https://img.qammunity.org/2023/formulas/mathematics/college/qhn382y1emsxc74jyjc2ujl751rc1auq9n.png)
..... eqn.4
3) Now add eqn.3 and eqn.4 to get the value of 'x' :-
![x + y + x - y = 3 + 1](https://img.qammunity.org/2023/formulas/mathematics/college/25a2g0rd17if4d3oy87dt2vmv795a3qbb9.png)
![=> 2x = 4](https://img.qammunity.org/2023/formulas/mathematics/college/tdnolfy2xf9aiv3digfhx176igjghsknx1.png)
![=> x = (4)/(2) = 2](https://img.qammunity.org/2023/formulas/mathematics/college/olfq86zwtnloepiksutcmjx0hk5pge252b.png)
4) Substitute the value of 'x' in either eqn.1 or eqn.2 and solve it to get the value of 'y' ( I'm here substituting it in eqn.1 ) :-
![4 * 2 +3y = 11](https://img.qammunity.org/2023/formulas/mathematics/college/a6lgy1xx2lti16h4x63c1p6bhxnj2xyz0a.png)
![=> 3y = 11 - 8 = 3](https://img.qammunity.org/2023/formulas/mathematics/college/gkybyw8a87clw3nlt61crxzhs97igkofmj.png)
![=> y = (3)/(3) = 1](https://img.qammunity.org/2023/formulas/mathematics/college/2xlo4pj7909enls797wwpojs4zdxylh68b.png)